The World as a City : A Philosophical Image between the Ancient World and the Three Monotheisms - Luca, Ludovica De,; Mecci, Stefano, (Ancient Philosophy & Religion ;, 2026)
The originality of the present book consists in hosting contributions which deal with the concept of cosmopolitanism and the metaphorical image of the world as a city. These issues are analyzed in their philosophical and religious dimension: Greek-Roman antiquity; Christianity from its origins to the 6th century; the post-Biblical and medieval Jewish tradition; the Islamic tradition up to the 12th century. Particularly, the volume investigates how the philosophical meaning of cosmopolitanism has been modified since its Cynic-Stoic origin: it focuses on its new (and not only theological) meanings inside the three monotheisms.